Expression profiling of auxin biosynthesis genes during inflorescence development in black pepper(Piper nigrum L) - Arathy L S (Department of plant biotechnology, college of agriculture, 2019)
The study entitled “Expression profiling of auxin biosynthesis genes during inflorescence development in black pepper (Piper nigrum L.)” was carried out during 2017-2019, in the Department of Plant Biotechnology, College of Agriculture, Vellayani. The objective of the study was to compare the transcript profile of auxin biosynthesis genes such as Flavin monooxygenase and Tryptophan aminotransferase during inflorescence development in different cultivars of black pepper (Piper nigrum L.) using Reverse Transcription quantitative PCR (RT- qPCR).